Pengembangan E-Module IPA Bermuatan Etnosains Pada Materi Usaha, Energi, dan Pesawat Sederhana Untuk Siswa SMP/MTs - Kadek Leony Agustini; Luh Mitha Priyanka; Putu Prima Juniartina (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
The limited variety and constraints of science teaching materials make the learning process tend to be monotonous, so students are less facilitated to develop deep understanding and critical thinking skills. Meanwhile, integration with ethnoscience has not been widely implemented, so the potential of local culture as a learning resource has not been optimally utilized. The aim of this study is to describe and analyze the characteristics, validity, and practicality of an ethnoscience-based science e-module on topics related to work, energy, and simple machines. The method used is the Research and Development (R&D) research method, with the development model used being 4D (Define, Design, Development, Disseminate). However, this research is limited to the development stage due to time constraints. The trial subjects consisted of two science education experts, three science teachers at SMPN 3 Banjar, and 10 students from SMPN 3 Banjar. The trial objects were validity and practicality tests using a questionnaire distribution. The characteristics found in the e-module are: 1) using local wisdom from the area, 2) presented in softcopy format as a flipbook. The content validity level of the developed e-module scored 0.97 with a very high qualification, and a score of 1.00 for media and language validity. The practicality level by teachers scored 83.4, and the score obtained for student practicality was 46.5, thus the practicality qualification is stated as very practical. Based on this, this e-module can be declared valid and practical.